Formulas and calculations for drilling, production, and workover : all the formulas you need to solve drilling and production problems - Lyons, William C.; Carter, Thomas; Lapeyrouse, Norton J. (Gulf Professional Publishing, 2022)
Updated for today's engineer, Formulas and Calculations for Drilling, Production, and Workover, Fifth Edition delivers the quick answers for daily petroleum challenges. Starting with a review of basic equations, calculations, and many worked examples, this reference offers a quick look up of topics such as drilling fluids, pressure control, and air and gas calculations. The formulas and calculations are provided in either English field units or in metric units. Additional topics include cementing, subsea considerations, well hydraulics, hydraulic fracturing methods, and drill string design limitations. New formulas include geothermal drilling, horizontal wells, and temperature workover. Formulas and Calculations for Drilling, Production, and Workover, Fifth Edition continues to save time and money for the oilfield worker and manager on the job with an easy layout and organization, helping you confidently conduct operations and evaluate the performance of your wells.